Deubiquitinase USP47-stabilized splicing factor IK regulates the splicing of ATM pre-mRNA - Ka, Hye In (Cell Death Discov, 2020)
IK depletion leads to an aberrant mitotic entry because of chromosomal misalignment through the enhancement of Aurora B activity at the interphase. Here, we demonstrate that IK, a spliceosomal component, plays a crucial role in the proper splicing of the ATM pre-mRNA among other genes related with the DNA Damage Response (DDR). Intron 1 in the ATM pre-mRNA, having lengths <200 bp, was not spliced in the IK-depleted cells and led to a deficiency of the ATM protein. Subsequently, the IK depletion-induced ATM protein deficiency impaired the ability to repair the damaged DNA. Because the absence of SMU1 results in IK degradation, the mechanism underlying IK degradation was exploited. IK was ubiquitinated in the absence of SMU1 and then subjected to proteolysis through the 26S proteasome. To prevent the proteolytic degradation of IK, a deubiquitinating enzyme, USP47, directly interacted with IK and stabilized it through deubiquitination. Collectively, our results suggest that IK is required for proper splicing of the ATM pre-mRNA and USP47 contributes toward the stabilization of IK.